Impact of the "when the fun stops, stop" gambling message on online gambling behaviour: a randomised, online experimental study. (May 2022) - Newall, Philip W S; Weiss-Cohen, Leonardo; Singmann, Henrik; Walasek, Lukasz; Ludvig, Elliot A
Summary: Background: Safer gambling messages are a common freedom-preserving method of protecting individuals from gambling-related harm. Yet, there is little independent and rigorous evidence assessing the effectiveness of safer gambling messages. In our study, we aimed to test the effect of the historically most commonly-used UK safer gambling message on concurrent gambling behaviour of people who gamble in the UK. Methods: In this study, three preregistered, incentivised, and randomised online experiments, testing the UK's "when the fun stops, stop" message, were carried out via the crowdsourcing platform Prolific. Adults based in the UK who had previously participated in the gambling activities relevant to each experiment were eligible to participate. Experiments 1 and 3 involved bets on real soccer events, and experiment 2 used a commercially available online roulette game. Safer gambling message presence was varied between participants in each experiment. In experiment 2, exposed participants could be shown either a yellow or a black-and-white version of the safer gambling message. Participants were provided with a monetary endowment with which they were allowed to bet. Any of this money not bet was afterwards paid to participants as a bonus, in addition to the payouts from any winning bets. In experiment 2 participants had the opportunity to re-wager any winnings from the roulette game. The primary outcome in experiment 1 was participants' decisions to accept (or reject) a series of football bets, which varied in their specificity (and payoffs), and the primary outcomes of experiments 2 and 3 were the proportion of available funds bet, which were defined as the total amount of money bet by a participant out of the total that could have been bet. Findings: Participants for all three experiments were recruited between May 17, 2019, and Oct 17, 2020. Of the 506 participants in experiment 1, 41·3% of available bets were made by the 254 participants in the gambling message condition, which was not significantly different (p=0·15, odds ratio 1·22 [95% CI 0·93 to 1·61]) to the 37·8% of available bets made by the 252 participants in the control condition. In experiment 2, the only credible difference between conditions was that the 501 participants in the condition with the yellow version of the gambling message bet 3·64% (95% Bayesian credibility interval 0·00% to 7·27%) more of available funds left over than the 499 participants in the control condition. There were no credible differences between the bets made by the 500 participants in the black-and-white gambling message condition and the other conditions. In experiment 3, there were no credible differences between the 502 participants in the gambling message condition and the 501 participants in the control condition, with the largest effect being a 5·87% (95% Bayesian credibility interval –1·44% to 13·20%) increase in the probability of betting everything in the gambling message condition. Interpretation: In our study, no evidence was found for a protective effect of the most common UK safer gambling message. Alternative interventions should be considered as part of an evidence-based public health approach to reducing gambling-related harm. Funding: University of Warwick, British Academy and Leverhume, Swiss National Science Foundation.